Regulation and entry into telecommunications markets - Bijl, Paul de 1967- (Cambridge University Press, 2002)
This book analyses telecommunications markets from early to mature competition, filling the gap between the existing economic literature on competition and the real-life application of theory to policy. Paul De Bijl and Martin Peitz focus on both the transitory and the persistent asymmetries between telephone companies, investigating the extent to which access price and retail price regulation stimulate both short- and long-term competition. They explore and compare various settings, such as non-linear versus linear pricing, facilities-based versus unbundling-based or carrier-select-based competition, non-segmented versus segmented markets. On the basis of their analysis, De Bijl and Peitz then formulate guidelines for policy. This book is a valuable resource for academics, regulators and telecommunications professionals. It is accompanied by simulation programs devised by the authors both to establish and to illustrate their results
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Telecommunication policy; Competition; Marktzugang; Telekommunikationsmarkt; Regulierung